Expanding the therapeutic landscape of minoxidil for androgenetic alopecia: topical, oral and sublingual formulations - Dias, Flavia Rodrigues; Yong, Shin Shen; FitzGerald, Holly; Sinclair, Rodney D.; Bhoyrul, Bevin (Frontiers in Pharmacology, 2026)
Androgenetic alopecia (AGA) is the most common form of non-scarring alopecia, affecting up to 80% of men and 50% of women by the age of 70. Minoxidil, initially developed as an oral antihypertensive, has become one of the most widely used therapies for AGA due to its safety and efficacy. This review presents an overview of current evidence on topical, oral and sublingual minoxidil. Topical minoxidil, the only FDA-approved treatment for AGA in both men and women, promotes hair growth through several proposed mechanisms described in the article. Randomised controlled trials show that 5% formulations consistently increase hair counts, although results vary due to differences in follicular sulfotransferase activity. Low-dose oral minoxidil (0.25–5 mg) has emerged as a practical option for patients unresponsive to topical therapy. Hypertrichosis is the most frequent adverse effect, while cardiovascular events are uncommon at low doses. Sublingual administration, a novel delivery route that bypasses first-pass metabolism, may enhance follicular bioavailability while limiting systemic exposure. Early evidence indicates similar efficacy to oral therapy, with a potentially lower risk of cardiovascular effects. Overall, topical minoxidil remains first line, while oral and sublingual formulations expand therapeutic options and support individualised management. Further large-scale, long-term studies are needed to define optimal dosing, confirm safety and determine whether sublingual administration offers consistent advantages over oral use.